Risk Assessment of Neonates by Neurologic Exam and Amplitude-Integrated Electroencephalography - J Gordon Millichap (Pediatric Neurology Briefs)
The value of an early neurologic examination and amplitude-integrated electroencephalography (a-EEG) in the early identification of term infants at risk for persistent encephalopathy was evaluated in 52 infants enrolled prospectively with evidence of intrapartum distress at the University of Texas Southwestern Medical Center, Dallas, TX.